The Evolution of Higher-Order Thinking Skills (HOTS) Research in Education: A Bibliometric Study - Loso Judijanto (Eastasouth Institute, 2026)
This study aims to examine the evolution of Higher-Order Thinking Skills (HOTS) research in education through a bibliometric approach. The study analyzes scientific publications indexed in major academic databases over a specific period using bibliometric techniques such as co-occurrence, overlay visualization, and density mapping through VOSviewer software. The results show that HOTS research has experienced significant development, with a primary focus on pedagogical aspects, particularly on students, learning strategies, and critical thinking. The co-occurrence analysis reveals that core themes such as higher-order thinking skills, students, and education dominate the research landscape, reflecting a significant focus on the learning process. Temporal visualization reveals a shift from basic educational concepts to more innovative approaches such as problem-based learning and technology-based learning. Recent trends demonstrate increasing attention to the integration of digital technologies, such as artificial intelligence and deep learning, in HOTS development. Meanwhile, the density analysis indicates that although traditional pedagogical themes remain dominant, new topics related to technology and assessment offer broad research opportunities. Overall, this study provides a comprehensive mapping of the intellectual structure and trends of HOTS research and suggests directions for future research in educational innovation and policy.